2001
DOI: 10.1111/j.1752-1688.2001.tb05530.x
|View full text |Cite
|
Sign up to set email alerts
|

SACRAMENTO RIVER FLOW RECONSTRUCTED TO A.D. 869 FROM TREE RINGS1

Abstract: A time series of annual flow of the Sacramento River, California, is reconstructed to A.D. 869 from tree rings for a long‐term perspective on hydrologic drought. Reconstructions derived by principal components regression of flow on time‐varying subsets of tree‐ring chronologies account for 64 to 81 percent of the flow variance in the 1906 to 1977 calibration period. A Monte Carlo analysis of reconstructed n‐year running means indicates that the gaged record contains examples of drought extremes for averaging p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
218
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(228 citation statements)
references
References 16 publications
9
218
0
1
Order By: Relevance
“…To test Dd 18 O=Dt as an indicator of change in the hydrologic balance, we compared the lake-based drought time series with a tree-ring-based reconstruction of river discharge from the western flank of the northern Sierra Nevada and with ages of stumps of trees that had (Meko et al, 1999); solid areas indicate drought periods. D. Ages of tree stumps killed by rising lake waters (Lawrence and Lawrence, 1961, Stine 1990.…”
Section: -110 Cal Yr Bpmentioning
confidence: 99%
See 2 more Smart Citations
“…To test Dd 18 O=Dt as an indicator of change in the hydrologic balance, we compared the lake-based drought time series with a tree-ring-based reconstruction of river discharge from the western flank of the northern Sierra Nevada and with ages of stumps of trees that had (Meko et al, 1999); solid areas indicate drought periods. D. Ages of tree stumps killed by rising lake waters (Lawrence and Lawrence, 1961, Stine 1990.…”
Section: -110 Cal Yr Bpmentioning
confidence: 99%
“…Vertical dashed lines indicate droughts that impacted more than one region. Northern Sierra discharge reconstruction from Meko et al (1998); southern Sierra precipitation reconstruction from Graumlich (1993); and northwestern New Mexico precipitation reconstruction from Grissino-Mayer (1996). illustrate such a negative excursion in d 18 O.…”
Section: -3430 Cal Yr Bpmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar responses are shown by the relationship between the annual runoff of the Yimin River and maximum temperature and seasonal/annual precipitation, as well as by the relationship between the regional tree-ring width chronology and these climatic factors (Table 2). For instance, the correlation coefficients associated with the April-September mean maximum temperature (T 4-9(max) ), the seasonal precipitation for April-September (P [4][5][6][7][8][9] ) and the annual precipitation from the previous August to the current July (P 8-7 ) were -0.406, 0.64 and 0.669, respectively, for the annual runoff of the Yimin River and -0.465, 0.381 and 0.619, respectively, for the RC. The similar correlation coefficients associated with P 4-9 (0.64) and calendar-year annual precipitation (P ann ) (0.674) for the annual runoff of the Yimin River indicated that the Yimin River annual runoff was dominated by the summer rainfall (one-half of the year) [28].…”
Section: Climate-growth Responsementioning
confidence: 99%
“…The statistical relationship between tree-ring index data and the hydroclimatic records of variables such as runoff and streamflow has been exploited to construct reconstructions that are hundreds of years in length for many parts of the world [5][6][7][8][9][10].…”
mentioning
confidence: 99%